Women Through Anti-Proverbs - Litovkina, Anna T. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines stereotypical traits of women as they are reflected in Anglo-American anti-proverbs, also known as proverb transformations, deliberate proverb innovations, alterations, parodies, variations, wisecracks, fractured proverbs, and proverb mutations. Through these sayings and witticisms the author delineates the image of women that these anti-proverbs reflect, her qualities, attributes and behavior. The book begins with an analysis of how women's role in the family, their sexuality and traditional occupations are presented in proverbs, and presents an overview of the genre of the anti-proverb. The author then analyses how this image of women is transformed in anti-proverbs, sometimes subverting, but often reinforcing the sexist bias of the original. This engaging work will appeal to students and scholars of humour studies, paremiology, gender studies, cultural studies, folklore and sociolinguistics alike.